The Effect of Drought on the Yield of Winter Barley Lines in the Great Cumania Region - Czimbalmas, Ágnes (Acta Agraria Debreceniensis, 2004)
Winter barley is the third most important fodder plant in Hungary after winter wheat and maize. Its accommodation to the changing climatic conditions – mainly to drought in Great Cumania, the driest region of our country is of great importance from the point of view of plant breeding and growing. The vegetation period of 2002/2003 can be considered to have been very droughty with 247.5 mm precipitation. According to our results six- rowed barley lines have better drought tolerance than two-rowed lines. The average yields of the six-rowed barley lines were 12-25 per cent higher than the yields of the two rowed lines. Due to the joint effect of delayed sowing and drought, significant yield depression was detected both in the case of the early and the medium maturity group, and assessable data could be gained only from 35 per cent of the total territory.